Moderating Effect of Presenteeism on Perceived Organizational Support and Job Engagement: A Systematic Attempt towards Development of Nomological Network. - Renusha, M. (Sabaragamuwa University of Sri Lanka, 2022)
Presenteeism is a novel concept in behavioural studies and largely focused on its prevalence, determinants and consequences on the well-being of both employees and organizations. Though there is a growing interest among academicians and practitioners in respect of the relationship/impact of organizational support practices and job engagement, there is a gap in the theoretical as well as empirical knowledge about the mediating or moderating effect of presenteeism on the relationship between organizational support practices and job engagement in the workplace. Thus, this paper systematically reviewed the literature and revealed that less attention has been paid to valuing the presenteeism of employees to enhance the job engagement of employees by the organizations even though this phenomenon commonly exists in practice. The objective of this paper was to propose a nomological network of moderating effect of presenteeism on perceived organizational support and job engagement based on a systematic review of the literature. The findings of the review resulted in identifying the relationship between perceived organizational support and job engagement and also identifying the moderating effect of presenteeism on the relationship between perceived organizational support and job engagement. Finally, this review proposes a nomological network which is useful to test and understand the relationships among the reviewed concepts empirically in the future.
Keywords: Job engagement; Perceived organizational support; Presenteeism